Travels in Manchuria and Mongolia : a feminist poet from Japan encounters prewar China - Yosano, Akiko, 1878-1942 (Columbia University Press, 2001)
Yosano Akiko (1878-1942) was one of Japan's greatest poets and translators from classical Japanese. Her output was extraordinary, including twenty volumes of poetry and the most popular translation of the ancient classic The Tale of Genji into modern Japanese. The mother of eleven children, she was a prominent feminist and frequent contributor to Japan's first feminist journal of creative writing, Seito (Blue stocking). In 1928 at a highpoint of Sino-Japanese tensions, Yosano was invited by the South Manchurian Railway Company to travel around areas with a prominent Japanese presen.
Keywords: Yosano, Akiko, -- 1878-1942 -- Travel -- China -- Manchuria.; Yosano, Akiko, -- 1878-1942 -- Travel -- Mongolia.; Yosano, Akiko, -- 1878-1942.; Yosano, Akiko, -- 1878-1942; Manchuria (China) -- Description and travel.; Mongolia -- Description and travel.; Electronic books.; Livres numériques.; e-books.; LITERARY CRITICISM -- Asian -- General.; LITERARY CRITICISM -- Asian -- Japanese.; Travel; China -- Manchuria; Mongolia